On the evolutionary status and pulsations of the recently discovered blue large-amplitude pulsators (BLAPs) - Romero, Alejandra Daniela (2018)
The blue large-amplitude pulsators (BLAPs) constitute a new class of pulsating stars. They are hot stars with effective temperatures of ∼30 000 K and surface gravities of log g ∼ 4.9, that pulsate with periods in the range 20−40 min. Until now, their origin and evolutionary state, as well as the nature of their pulsations, were not been unveiled. In this paper, we propose that the BLAPs are the hot counterpart of the already known pulsating pre-extremely low mass (pre-ELM) white dwarf (WD) stars, that are He-core low-mass stars resulting from interacting binary evolution. Using fully evolutionary sequences, we show that the BLAPs are well represented by pre-ELM WD models with high effective temperature and stellar masses ∼0.34 M⊙. From the analysis of their pulsational properties, we find that the observed variabilities can be explained by high-order non-radial g-mode pulsations or, in the case of the shortest periods, also by low-order radial modes, including the fundamental radial mode. The theoretical modes with periods in the observed range are unstable due to the κ mechanism associated with the Z-bump in the opacity at log T ∼ 5.25.